ANALISIS KINERJA MESIN PEMARUT SAGU - Parenden, Daniel; Suwarjono, Suwarjono; Cipto, Cipto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Sago plantations are spread in almost all regions in Indonesia, such as Sulawesi, Kalimantan, Sumatra, Papua and Maluku with a land area of approximately 1,128 million Ha, which means that 51.3% of the world's sago is in Indonesia. Papua, including Merauke, is a district at the eastern tip of Indonesia that has the greatest potential for sago plantations in the world, reaching 5.5 million hectares. One of the villages in Merauke that has lots of sago plants is Kampung Kweel, which is located at the head of the Maro River. The Sago Farming Community in Kweel Village, performs sago processing, without using machines, so the results obtained are not optimal. The use of sago processing machines can streamline the sago production process. Processing sago with the application of sago grater machine technology is capable of producing grated sago pith from 279 kg/hour to 610.8 kg/hour, with a starch yield percentage of 37.91%.